2019
DOI: 10.3390/agronomy9030137
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Secondary Metabolites and Enzyme Activity Responses of Two Edible Fern Species to Drought Stress and Rehydration in Northeast China

Abstract: The drought resistance mechanism of Matteuccia struthiopteris (L.) Todar. and Athyrium multidentatum (Doll.) Ching were measured under natural drought exposure. The results showed that the two edible fern species showed stronger resistance in the early stages of drought, mainly expressed as the decrease of relative leaf water content (RLWC), increase of osmotic substances, secondary metabolites such as flavonoids (FC), total phenols (TPC), proantho cyanidins (PCC) content and enzyme activity (superoxide dismut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Some studies have found that when Salvinia species are stressed by heavy metals, they can accumulate phenolic compounds against oxidative damage caused by heavy metals (Prado et al, 2016;Prado et al, 2013). Our previous study found that when AM, MS and Adonis species are subjected to drought stress, phenolic compounds can also be accumulated to alleviate the oxidative damage caused by drought (Gao et al, 2020;Wang et al, 2019). In the present study, total phenols and flavonoids increased with the increase of light intensity, and were significantly positively correlated with hydrogen peroxide content, indicating that secondary metabolites such as phenolic compounds are important for alleviating ferns' oxidative damage.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have found that when Salvinia species are stressed by heavy metals, they can accumulate phenolic compounds against oxidative damage caused by heavy metals (Prado et al, 2016;Prado et al, 2013). Our previous study found that when AM, MS and Adonis species are subjected to drought stress, phenolic compounds can also be accumulated to alleviate the oxidative damage caused by drought (Gao et al, 2020;Wang et al, 2019). In the present study, total phenols and flavonoids increased with the increase of light intensity, and were significantly positively correlated with hydrogen peroxide content, indicating that secondary metabolites such as phenolic compounds are important for alleviating ferns' oxidative damage.…”
Section: Discussionmentioning
confidence: 98%
“…The photosynthetic capacity is negatively correlated with the leaf phenolic concentration 48 and this has been suggested to represent the gradient between a maximum carbon gain and maximum protection 49 , reflecting the trade-off between growth and defence/protection demands, depending on the growth strategy adopted by each species 48 . The phenolic compounds which are found mainly in the vacuole of several cells types in the leaves act as multifunctional specialized metabolites under abiotics stress 49 , such as non-enzymatic antioxidants 50 and repair of membrane from lipid peroxidation 51 . Several author have found that water stressed plants showed an increase in total phenols and flavonoids 20,26 , which suggests that the increased synthesis of these substances by plants represents an important defense mechanism of drought tolerance 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, understanding the positive effect of AMF on this species is crucial for its use in grassland rehabilitation and restoration. Our previous studies showed a good symbiotic relationship between AMF and this species under salt and alkali stresses ( Lin et al, 2017 ; Wang et al, 2019a ; Wang et al, 2019b Wang et al, 2019c ; Yang et al, 2020a ; Yang et al, 2020b ). In the present study, we hypothesized (1) that AMF play an important role in alleviating the inhibitory effect on seedling growth under alkali or drought stress conditions and (2) that the interaction of alkali and drought stresses affects the alleviating effect of AMF in Leymus chinensis seedlings.…”
Section: Introductionmentioning
confidence: 85%
“…Thiobarbituric acid (0.6%. one mL) was used to extract malondialdehyde (MDA) from fresh shoots (200 mg), and the absorbance was then measured at 600, 532 and 450 nm ( Wang et al, 2019a ; Wang et al, 2019b Wang et al, 2019c ). Proline was extracted with 3% sulfosalicylic acid for 1 h, and the absorbance was measured at 520 nm ( Bates, Waldren & Teare, 1973 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation